Children in migration and international family law : the child's best interests principle at the interface of migration law and family law - Arnold, Stefan; Heiderhoff, Bettina (Springer, 2025)
This open access book offers readers a better understanding of the legal situation of children and families migrating to the EU. Shedding light on the legal, practical, and political difficulties at the intersection of international family law and migration law, it demonstrates that enhanced coordination between these policy areas is crucial to improving the legal situation of families on the move. It not only raises awareness of these "interface" issues and the need for stakeholders in migration law and international family law to collaborate closely, but also identifies deficits in the statutory framework and suggests possible remedies in the form of interpretation and regulatory measures. The book is part of the EU co-financed FAMIMOVE project and includes contributions from international experts, who cover topics such as guardianship, early marriage, age assessment, and kafala from a truly European perspective. The authors' approach involves a rigorous analysis of the relevant statutory framework, case law, and academic literature, with particular attention given to the best interest of the child in all its facets. The book examines how this principle can be more effectively applied and suggests ways to foster a more fruitful understanding of its regulatory potential. Given its scope and focus, the book will be of interest to researchers, scholars, and practitioners of Private International Law, Family Law, and Migration Law. It makes a valuable contribution to these fields, particularly at their often-overlooked intersections.